Understanding the implication of Kawakita model parameters using in-die force-displacement curve analysis for compacted and non-compacted API powders - Iyad Rashid; Rula Raji Haddadin; Ashaar Abdulsalam Alkafaween; Rawan Nayef Alkaraki; Rehan Mohammad Alkasasbeh (SpringerOpen, 2022)
Abstract The aim of this study was to investigate powder mechanics upon compression using data obtained from force-displacement (F-D) curves. The Kawakita model of powder compression analysis was adopted in order to compare the pressure-volume reduction relationship of the drug powders in relation to the F-D curves. Experiments were carried out on six model drugs (metronidazole, metformin, secnidazole, ciprofloxacin, norfloxacin, and mebeverine). The drugs were compressed at different pressures in the non-processed or processed (using a roller compactor) forms. Results indicate the similarity between the F-D curves and a rearranged form of the Kawakita model. The foregoing enables the calculation of two important powder parameters, "a" (maximum powder volume reduction) and "P k " (pressure required to achieve half of the maximum volume reduction) from the F-D curves without the need, as in the case of the conventional Kawakita model, to compress powders into tablets at different compression forces. Graphical abstract